Acting without being in control: Exploring volition in Parkinson's disease with impulsive compulsive behaviours. (July 2017) - Ricciardi, Lucia; Haggard, Patrick; de Boer, Lieke; Sorbera, Chiara; Stenner, Max-Philipp; Morgante, Francesca; Edwards, Mark J.
Abstract: Background: Several aspects of volitional control of action may be relevant in the pathophysiology of impulsive-compulsive behaviours (ICB) in Parkinson's disease (PD). We aimed to explore multiple aspects of action control, assessing reward-related behaviour, inhibition (externally and internally triggered) and sense of agency in PD patients, with and without ICB compared to healthy subjects. Methods: Nineteen PD patients with ICB (PD-ICB), 19 PD without ICB (PD-no-ICB) and 19 healthy controls (HC) underwent a battery of tests including: Intentional Binding task which measures sense of agency; Stop Signal Reaction Time (SSRT) measuring capacity for reactive inhibition; the Marble task, assessing intentional inhibition; Balloon Analog Risk Task for reward sensitivity. Results: One-way ANOVA showed significant main effect of group for action binding (p = 0.004, F = 6.27). Post hoc analysis revealed that PD-ICB had significantly stronger action binding than HC (p = 0.004), and PD-no-ICB (p = 0.04). There was no difference between PD-no-ICB and HC. SSRT did not differ between PD groups, whereas a significant difference between PD-no-ICB and HC was detected (p = 0.01). No other differences were found among groups in the other tasks. Conclusions: PD patients with ICB have abnormal performance on a psychophysical task assessing sense of agency, which might be related to a deficit in action representation at cognitive/experiential level. Yet, they have no deficit on tasks evaluating externally and internally triggered inhibitory control, or in reward-based decision-making. We conclude that impaired sense of agency may be a factor contributing to ICB in PD patients. Highlights: We assessed the relationship between impulsive-compulsive behavior (ICB) and action control in PD. PD-ICB have abnormally strong action binding. This effect remained significant when correcting for disease duration and LEDD. The abnormality of action binding suggests that impaired sense of agency is related to ICB in PD.